Thymic cysts originate from Foxn1 positive thymic medullary epithelium. - Vroegindeweij, E; Crobach, S; Itoi, M; Satoh, R; Zuklys, S; Happe, C; Germeraad, W; Cornelissen, J; Cupedo, T; Holländer, G; Kawamoto, H; van Ewijk, W (2010)
Thymic epithelial cells (TECs), derived from polarized two-dimensional (2D) oriented endodermal cells, are distinguished from other epithelial cells by their unique three-dimensional (3D) phenotype. However, some polarized epithelial cells remain present in the normal thymus, forming thymic cysts at the cortico-medullary junction. Here, we analyse the dynamics, origin and phenotype of such thymic cysts. In time-course experiments, we show a reverse correlation between thymic cyst expansion and the presence of thymocytes, suggesting a default pathway for the development of TECs in the absence of thymocytes. By transplanting isolated TEC populations into E15 fetal thymic lobes, we provide evidence that medullary thymic epithelial cells (mTECs), rather than cortical thymic epithelial cells (cTECs) contribute to the formation of thymic cysts. Finally, thymi of reporter mice reveal that the cysts originate from epithelia committed to a thymic fate, as indicated by the expression of Foxn1. The 2D-phenotype of cyst-lining TECs is not caused by a downregulation of Foxn1 expression, since a significant proportion of these cells in the embryonic and adult thymus continues to express Foxn1 at the protein level.